Proceso de atención nutricional en paciente femenina de 21 años de edad con helicobacter pylori . - Guayaquil Cobo, Mishell Lizbeth (2022)
Helicobacter pylori infection is a global health problem; According to studies, 70% of Ecuadorians have Helicobacter Pylori. H. Pylori is known as a Gram-negative bacillus that is found in the gastric mucosa of human beings, being the origin of various pathologies. The nutritional care process performed on the 21-year-old female patient with Helicobacter Pylori, which was confirmed by various tests. Through the anthropometric assessment, weight and height were obtained, values that helped us to give a nutritional diagnosis, the patient has a low weight according to her BMI. The biochemical values reflected values outside the normal ranges with regard to hemoglobin, hematocrit and MCV, therefore, it is confirmed that the patient has anemia. The dietary evaluation showed us a low caloric intake, also the infection is related to bad eating habits that were predominant in the appearance and development of Helicobacter Pylori. The correct nutritional intervention to the patient, a notable decrease in the signs and symptoms of the pathology was achieved, in the same way the patient reached a normal weight according to the parameters established by the BMI; blood tests showed that the patient had hemoglobin, hematocrit and MCV within normal ranges; in the dietary aspect, eating habits were improved.